Authenticity and interest in virtual reality: Findings from an experiment including educational virtual environments created with 3D modeling and photogrammetry - Fink, Maximilian C.; Sosa, Diana; Eisenlauer, Volker; Ertl, Bernhard (Frontiers in Education, 2023)
Virtual Reality (VR) and photogrammetry are emerging technologies that facilitate and shape the ongoing digital transformation of education. VR offers new opportunities for creating immersive and interactive educational experiences. Photogrammetry enables new ways to create lifelike educational virtual environments and is becoming an alternative to manual 3D modeling with graphics software. The manner in which VR affects the authenticity of educational experiences has been addressed in previous educational and psychological research. Empirical papers have so far focused on the authenticity of educational VR environments created by 3D modeling. However, little is known about the authenticity of educational VR environments developed with photogrammetry. Given that VR provides rich multi-sensory experiences and interests can be stimulated by engaging contexts, educational VR environments also possess great potential to support interest development. What is still unknown regarding this topic are the beneficial characteristics of VR environments and the individual variables required to trigger and explain interest development. Consequently, we conducted an experiment following up on the mentioned authenticity and interest research questions in the context of higher education. A two-group between-subjects design was used and N = 64 educational science and psychology university students gathered information about a railroad bridge wearing a head-mounted display (HMD). The control group encountered an educational virtual environment created with 3D modeling. The intervention group was presented with the same educational virtual environment but the main object of the railroad bridge was generated by photogrammetry. Situational interest was measured in the pretest and the posttest; authenticity-related variables (i.e., presence and representation fidelity) were assessed in the posttest. Concerning authenticity, there were no significant group differences. Photogrammetry might thus not affect authenticity in educational contexts in which participants focus on gathering information. Regarding interest development, there were two main findings. First, interest in VR for learning increased from pretest to posttest, supporting that interest can be induced in VR. Second, a large share of posttest interest was explained by presence and pretest interest, highlighting the importance of these variables.